Is your privacy for sale? An experiment on the willingness to reveal sensitive information - Janis Cloos; Björn Frank; Lukas Kampenhuber; Stephany Karam; Nhat Luong; Daniel Möller; Maria Monge-Larrain; Nguyen Tan Dat; Marco Nilgen; Christoph Rössler (Games, 2019)
10.3390/g10030028
Keywords: D72; D83; M37; 330; privacy; personal data; social disapproval; WTA experiment; donation experiment